COMMUNITY SERVICE BUILDING YOUTH AWARENESS OF NARKOLEMA [Narcotics Through The Eyes] THROUGH SOCIALIZATION AND EDUCATION - Danyl Mallisza; Slamet Riyadi; Nur Adilah; Nazili, Nazili; Al Azhar; Aulia Rizki Alda (Ikatan Dosen Menulis, 2024)
The development of digital technology has had both positive and negative impacts on society, especially teenagers. One of the emerging threats is Narcolemma (Narcotics Through the Eyes), namely exposure to negative content through digital devices that can influence teenagers' thought patterns and behavior. Content that promotes narcotics, free lifestyles and destructive actions is increasingly easily accessed via social media and the internet without adequate supervision. Therefore, Ekasakti University and its team carry out community service activities with the aim of increasing youth awareness and understanding regarding the dangers of narcotics and building digital resilience. The method used in this activity is digital literacy-based counseling and education. Some of the activities carried out include seminars and interactive discussions, training for parents and educators, creating educational media, and establishing Digital Anti-Narcolemma Ambassadors. The results of the activity show that teenagers have become more aware of the negative impacts of dangerous digital content and are able to filter information more wisely. Apart from that, the participation of parents and teachers also contributes to creating a safer environment for teenagers when using technology. The sustainability of this program is realized through collaboration with various parties, including educational institutions, youth communities and government agencies. With this activity, it is hoped that the younger generation will be smarter, wiser and more responsible in facing the digital era and distance themselves from the negative influence of Narcolemma.